Supported on mesoporous silica nanospheres, molecularly imprinted polymer for selective adsorption of dichlorophen - Ma Yuxuan (De Gruyter, 2021)
The imprinted polymers were prepared to absorb dichlorophen (DCP) by using mesoporous silica with ordered pores and high specific surface area. Both scanning electron microscopy and transmission electron microscopy results suggested that the mesoporous silica nanosphere pores had a periodic distribution. The imprinted layer of polymers was thin and uniform. The adsorption experiments showed that the adsorption of imprinted polymers was obviously improved due to the presence of mesoporous structure. The maximum adsorption capacity of MSNs@MIPs at 318 K was 91.1 mg/g, and the adsorption process rapidly reached the equilibrium within 40 min. The adsorption isotherm was well fitted by the Freundlich isotherm model, indicating that multimolecular layer adsorption mechanism governs the adsorption of DCP by the polymers. The adsorption of MSNs@MIPs complied with pseudo-second-order kinetic model. Both selective and regenerative experiments demonstrated that MSNs@MIPs can be successfully applied for selective adsorption of DCP.